Injection-molded bonded ferrite magnet and method for producing same, Hybrid magnetic circuit structure

CN123017667APending Publication Date: 2026-10-30EXTREME LIGHT POWER (BEIJING) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611260808.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明的核心创新包括三个递进层次:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017667A_ABST
    Figure CN123017667A_ABST
Patent Text Reader

Abstract

The application provides an injection-molded bonded ferrite magnet and a preparation method and a mixed magnetic circuit structure thereof, and belongs to the technical field of magnetic functional composite materials. Alpha-Fe2O3 and inorganic compound additives are sequentially mixed and pre-burned, ferrite magnetic powder is mixed with a silane coupling agent for surface pretreatment, surface-activated ferrite magnetic powder is added into a functionalized SWCNT dispersion liquid for liquid-phase composite reaction, ferrite@SWCNT composite powder is sequentially blended, granulated, injection-molded and magnetized with a thermoplastic polymer bonding matrix. The application limits the particle size of alpha-Fe2O3, realizes precise control of ferrite grain morphology, size distribution and magnetic crystal anisotropy in the pre-burning stage, and combines high coercivity and high remanence, and combines with functionalized metal single-walled carbon nanotubes, so that the prepared injection-molded bonded ferrite magnet can be used cooperatively with a rare earth permanent magnet, and the rare earth magnet is replaced in a magnetic field sparse area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetic functional composite materials technology, and in particular to an injection-molded bonded ferrite magnet, its preparation method, and a hybrid magnetic circuit structure. Background Technology

[0002] Bonded ferrite permanent magnets have been widely used in micro stepper motors, brushless DC motor rotors, and sensor magnetic rings due to their advantages such as low cost, high degree of shape freedom, and the ability to integrally injection mold complex magnetic circuit structures. Traditional bonded ferrite magnets typically use strontium ferrite (SrFe). 12 O 19 ) or barium ferrite (BaFe 12 O 19 The powder is used as a magnetic filler, and thermoplastic polymers such as nylon 6 (PA6), nylon 12 (PA12) or polyphenylene sulfide (PPS) are used as the binder matrix. It is prepared by injection molding. In this type of system, the filling ratio of magnetic filler usually needs to reach 88~94wt% to obtain the magnetic properties that meet the requirements. However, such a high content of inorganic filler brings a series of technical problems: (1) poor melt flow and difficult molding. (2) insufficient mechanical properties of magnets. (3) limited space for improving magnetic properties. (4) poor thermal conductivity. (5) insufficient intrinsic properties of ferrite magnetic powder.

[0003] In recent years, carbon nanotubes (CNTs), as one-dimensional nanomaterials, such as single-walled carbon nanotubes (SWCNTs), have attracted much attention due to their ultra-high aspect ratio, excellent mechanical properties (tensile strength 10~60 GPa, elastic modulus about 1 TPa), and good electrical and thermal conductivity (the thermal conductivity of a single SWCNT can reach 3500 W / (m·K)). Existing technologies show that adding a small amount of CNTs to polymer composites can significantly improve the mechanical strength, electrical conductivity, and thermal conductivity of the material. However, directly introducing CNTs into highly filled ferrite / polymer systems faces significant challenges: CNTs are prone to agglomeration in polymer melts, making uniform dispersion difficult, and there is a lack of effective interfacial interaction between CNTs and ferrite particles, preventing the formation of a synergistically reinforcing composite structure. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide an injection-molded bonded ferrite magnet, its preparation method, and a hybrid magnetic circuit structure. By limiting the particle size of α-Fe₂O₃, this invention achieves precise control over the morphology, size distribution, and magnetocrystalline anisotropy of ferrite grains during the pre-sintering stage, balancing high coercivity and high remanence. Combined with functionalized metallic single-walled carbon nanotubes, a ferrite / SWCNT composite structural unit is formed. The resulting injection-molded bonded ferrite magnet can be used in conjunction with rare-earth permanent magnets, replacing rare-earth magnets in regions with sparse magnetic field lines.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing an injection-molded bonded ferrite magnet, comprising the following steps: α-Fe2O3 and inorganic compound additives are mixed and pre-calcined sequentially to obtain ferrite magnetic powder, wherein the particle size of α-Fe2O3 is 10nm~200μm; The ferrite magnetic powder is mixed with a silane coupling agent and subjected to surface pretreatment to obtain surface-activated ferrite magnetic powder. A functionalized metal-type single-walled carbon nanotube dispersion is provided; wherein the functionalized metal-type single-walled carbon nanotubes in the dispersion are metal-type single-walled carbon nanotubes that have undergone functional group activation treatment and surfactant treatment. The surface-activated ferrite magnetic powder was added to a functionalized metal single-walled carbon nanotube dispersion to carry out a liquid-phase composite reaction, thereby obtaining ferrite@SWCNT composite powder. The ferrite@SWCNT composite powder and the thermoplastic polymer binder matrix are sequentially blended, granulated, injection molded, and magnetized to obtain the injection-molded bonded ferrite magnet.

[0006] Preferably, the α-Fe2O3 comprises the following components in parts by mass: 5-20 parts by mass of nano-sized α-Fe2O3, 50-80 parts by mass of submicron-sized α-Fe2O3, and 10-30 parts by mass of micron-sized α-Fe2O3. The particle size of the nano-sized α-Fe2O3 is 10-500 nm, the particle size of the submicron-sized α-Fe2O3 is 0.5-10 μm, and the particle size of the micron-sized α-Fe2O3 is 10-200 μm.

[0007] Preferably, the inorganic compound additive includes one or more of SrCO3, BaCO3, La2O3, Co2O3, Co3O4, and flux.

[0008] Preferably, the pre-firing temperature is 1100~1320℃ and the time is 1~4h.

[0009] Preferably, the functional groups used in the functional group activation treatment include one or more of amino, carboxyl, and ester groups.

[0010] Preferably, the raw materials, based on surface-activated ferrite magnetic powder, functionalized metallic single-walled carbon nanotubes, and thermoplastic polymer binder matrix, include the following components by mass percentage: 80-93% surface-activated ferrite magnetic powder, 0.05-3% functionalized metallic single-walled carbon nanotubes, and 6.95-17% thermoplastic polymer binder matrix.

[0011] Preferably, the raw material further includes processing aids, wherein the mass percentage of the processing aids in the raw material is 0-2% and not 0.

[0012] Preferably, the temperature of the liquid-phase composite reaction is 20~80℃ and the time is 0.5~4h.

[0013] The present invention also provides an injection-molded bonded ferrite magnet prepared by the preparation method described above, comprising functionalized metallic single-walled carbon nanotubes and ferrite magnetic powder particles. The functionalized metallic single-walled carbon nanotubes exist in a core-shell coating layer on the surface of the ferrite magnetic powder particles and / or in a network distribution morphology penetrating between the ferrite magnetic powder particles. The ferrite magnetic powder particles have a bimodal grain size distribution, and the ferrite magnetic powder particles include small grains and large grains. The small grains have a grain size of 0.5~2μm, and the large grains have a grain size of 3~10μm.

[0014] The present invention also provides a hybrid magnetic circuit structure, comprising the injection-molded bonded ferrite magnet and rare-earth permanent magnet described in the above technical solution.

[0015] This invention provides a method for preparing an injection-molded bonded ferrite magnet, comprising the following steps: sequentially mixing and pre-calcining α-Fe2O3 and inorganic compound additives to obtain ferrite magnetic powder, wherein the particle size of the α-Fe2O3 is 10nm~200μm; mixing the ferrite magnetic powder with a silane coupling agent for surface pretreatment to obtain surface-activated ferrite magnetic powder; providing a functionalized metal-type single-walled carbon nanotube dispersion; wherein the functionalized metal-type single-walled carbon nanotubes in the functionalized metal-type single-walled carbon nanotube dispersion are metal-type single-walled carbon nanotubes that have undergone functional group activation treatment and surfactant treatment; adding the surface-activated ferrite magnetic powder to the functionalized metal-type single-walled carbon nanotube dispersion for a liquid-phase composite reaction to obtain ferrite@SWCNT composite powder; sequentially blending and granulating the ferrite@SWCNT composite powder with a thermoplastic polymer bonding matrix, injection molding, and magnetizing to obtain the injection-molded bonded ferrite magnet.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: The core innovation of this invention includes three progressive levels: (I) Raw material-level performance control of ferrite magnetic powder. Using α-Fe₂O₃ with multiple morphologies and particle size distributions as a precursor, combined with inorganic compound additives, precise control of ferrite grain morphology, size distribution, and magnetocrystalline anisotropy was achieved during the pre-sintering stage. The mixed design of multi-size precursors resulted in a bimodal grain size distribution after pre-sintering, balancing high coercivity and high remanence.

[0017] (II) Construction of Structured Interfaces for Functionalized Metallic SWCNTs. A structured composite interface is pre-constructed between functionalized metallic SWCNTs and surface-activated ferrite magnetic powder in a liquid-phase composite reaction, forming a ferrite / SWCNT composite structural unit. Compared with the traditional direct mechanical mixing method, this method has the following advantages: Uniform dispersion of functionalized SWCNTs: In the liquid medium, functionalized SWCNTs are fully deagglomerated and then uniformly anchored at the nanoscale through directional interfacial interaction with surface-activated ferrite magnetic powder, avoiding reagglomeration in subsequent melt blending. Synergistic enhancement effect: Functionalized SWCNTs form a nanoscale stress transfer layer at the ferrite magnetic powder-polymer interface, which dissipates fracture energy through crack bridging and pull-out mechanisms, significantly improving mechanical properties; the continuous thermally conductive network between particles of functionalized SWCNTs provides an efficient channel for phonon transport, improving thermal conductivity. Improved processing fluidity: The functionalized SWCNT coating acts as a solid lubricant, reducing interparticle frictional resistance and melt viscosity in highly filled melts during injection molding.

[0018] (III) Cost Reduction Application of Hybrid Magnetic Circuits. The low-cost injection-molded bonded ferrite magnets obtained by this invention can be used in conjunction with high-cost rare-earth permanent magnets (such as sintered NdFeB and SmCo) in motor magnetic circuits. High-performance rare-earth permanent magnets are used in the working air gap region where magnetic lines of force are dense, while the injection-molded bonded ferrite magnets of this invention are used in the magnetic pole edges, leakage magnetic regions, and auxiliary magnetic circuit parts where magnetic lines of force are sparse. Taking a typical 100kW permanent magnet synchronous drive motor as an example, after adopting this hybrid magnetic circuit scheme, the amount of rare-earth permanent magnets used can be reduced by 20% to 35%, the total material cost of the magnets can be reduced by 25% to 40%, while the overall performance of the motor (torque density, efficiency) decreases by no more than 3%.

[0019] The data from the examples show that: The intrinsic coercivity Hcj of injection-molded bonded ferrite magnets is increased by 15% to 80% compared to magnetic powders prepared from traditional single-particle-size precursors (depending on the doping system). The flexural strength of injection-molded bonded ferrite magnets is 30-120% higher than that of ferrite / polymer magnets with the same filler content but without functionalized SWCNTs. The impact strength of injection-molded bonded ferrite magnets is increased by 40% to 300%; Melt flow index (MFI) increases by 15-80% during injection molding; The remanence (Br) retention rate of injection-molded bonded ferrite magnets is ≥95%, and the magnetic energy product (BHmax) retention rate is ≥92%. The thermal conductivity of injection-molded bonded ferrite magnets is increased by 10-200%; The mechanical properties of injection-molded bonded ferrite magnets after heat aging at 150℃ / 1000h retain ≥85%; In the hybrid magnetic circuit scheme, the amount of rare earth permanent magnets used is reduced by 20% to 35%, and the total magnet material cost is reduced by 25% to 40%.

[0020] The present invention also provides a method for preparing the injection-molded bonded ferrite magnet described in the above technical solution. The preparation method of the present invention is simple to operate and suitable for industrial application. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the injection-molded bonded ferrite magnet described in this invention; Figure 2 This is a flowchart illustrating the preparation of injection-molded bonded ferrite magnets in an embodiment of the present invention; Figure 3 A schematic diagram showing the distribution of high-performance permanent magnets and injection-molded bonded ferrite magnets; Figure 4 Here is a SEM image of nano-sized α-Fe2O3 from Example 1; Figure 5 This is a SEM image of submicron-sized α-Fe2O3 in Example 1; Figure 6 This is a SEM image of micron-sized α-Fe₂O₃ in Example 1; Figure 7 Here is a SEM image of the ferrite magnetic powder in Example 1; Figure 8 Here is a SEM image of the SF-1@SWCNT composite powder in Example 1; In the figure, ① represents ferrite magnetic powder particles, ② represents functionalized metallic single-walled carbon nanotubes, and ③ represents thermoplastic polymer binder matrix. Detailed Implementation

[0022] This invention provides a method for preparing an injection-molded bonded ferrite magnet, comprising the following steps: α-Fe2O3 and inorganic compound additives are mixed and pre-calcined sequentially to obtain ferrite magnetic powder, wherein the particle size of α-Fe2O3 is 10nm~200μm; The ferrite magnetic powder is mixed with a silane coupling agent and subjected to surface pretreatment to obtain surface-activated ferrite magnetic powder. A functionalized metal-type single-walled carbon nanotube dispersion is provided; wherein the functionalized metal-type single-walled carbon nanotubes in the dispersion are metal-type single-walled carbon nanotubes that have undergone functional group activation treatment and surfactant treatment. The surface-activated ferrite magnetic powder was added to a functionalized metal single-walled carbon nanotube dispersion to carry out a liquid-phase composite reaction, thereby obtaining ferrite@SWCNT composite powder. The ferrite@SWCNT composite powder and the thermoplastic polymer binder matrix are sequentially blended, granulated, injection molded, and magnetized to obtain the injection-molded bonded ferrite magnet.

[0023] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field.

[0024] This invention involves sequentially mixing and pre-calcining α-Fe2O3 and inorganic compound additives to obtain ferrite magnetic powder. The particle size of the α-Fe2O3 is 10nm~200μm, and the α-Fe2O3 (iron red) is an iron source precursor. Depending on the target ferrite type, different inorganic compound additives are added to generate high-performance ferrite magnetic powder through in-situ reaction during the pre-calcination stage.

[0025] In this invention, the α-Fe₂O₃ preferably comprises the following components in parts by mass: 5-20 parts by mass of nano-sized α-Fe₂O₃, 50-80 parts by mass of submicron-sized α-Fe₂O₃, and 10-30 parts by mass of micron-sized α-Fe₂O₃. The nano-sized α-Fe₂O₃ has a particle size of 10-500 nm. The nano-sized α-Fe₂O₃ provides a high specific surface area and reactivity, promotes the full progress of the solid-phase reaction during the pre-calcination stage, and is beneficial for the formation of fine and uniform ferrite grains. The submicron-sized α-Fe₂O₃ has a particle size of 0.5-10 μm. α-Fe₂O₃ serves as the main reactant, providing the primary iron source required for ferrite formation. The micron-sized α-Fe₂O₃ has a particle size of 10~200μm and acts as a framework template, partially retaining the original particle morphology during pre-calcination, which helps to form favorable texture and orientation in the ferrite powder. By controlling the mixing ratio of α-Fe₂O₃ with different particle sizes, ferrite powder with a bimodal grain size distribution is obtained after pre-calcination. Small grains (0.5~2μm) provide high coercivity, while large grains (3~10μm) provide high remanence, thus achieving an optimal balance between remanence and coercivity.

[0026] In this invention, the morphology of the α-Fe2O3 preferably includes one or more of spherical, sheet-like, needle-like, and rod-like shapes, more preferably sheet-like, to obtain better orientation and remanence. The nanoscale α-Fe2O3 is more preferably spherical, the submicron-scale α-Fe2O3 is more preferably spherical, and the micron-scale α-Fe2O3 is more preferably sheet-like or needle-like.

[0027] In this invention, the inorganic compound additive preferably includes one or more of SrCO3, BaCO3, La2O3, Co2O3, Co3O4 and flux.

[0028] In this invention, the target ferrite type preferably includes the system A-SrFe. 12 O 19 (Strontium ferrite), system B-BaFe 12 O 19 (Barium ferrite) and the system CLa-Co doped strontium ferrite Sr 1-x La x Fe 12-y Co y O 19 x satisfies 0.1≤x≤0.5, y satisfies 0.1≤y≤0.4, and the substitution amount of La and the substitution amount of Co satisfy y=(0.8~1.2)x to maintain lattice charge balance.

[0029] In this invention, system A preferably comprises the following raw materials by mass percentage: α-Fe₂O₃ 87~91% (more preferably 87.5~91%), SrCO₃ 7~9% (more preferably 7.5~8%), and CaCO₃ 1~5% (more preferably 2~4%). The CaCO₃ acts as a flux and grain growth regulator, decomposing into CaO during the pre-calcination process, with some CaO... 2+ Entering SrFe 12 O 19 Lattice Substitution of Sr 2+ The site optimizes the grain morphology and inhibits abnormal grain growth, while reducing the pre-sintering temperature by 50~100℃.

[0030] In this invention, system B preferably comprises the following raw materials in the following mass percentages: α-Fe2O3 82%, BaCO3 18%.

[0031] In this invention, system C preferably comprises the following raw materials by mass percentage: α-Fe₂O₃ 80~88% (more preferably 82~86%), SrCO₃ 5~12% (more preferably 9~11%), CaCO₃ 3~10% (more preferably 4~7%), La₂O₃ 1~3% (more preferably 2~3%), and cobalt oxide 1~3% (more preferably 1.5~2.5%), wherein the cobalt oxide preferably comprises Co₂O₃ and / or Co₃O₄, and during the pre-calcination process, La… 3+ Partially replaces Sr 2+ Site, Co 2+ / Co 3+ Partially replaces Fe 3+The site and the joint substitution mechanism significantly enhance the magnetocrystalline anisotropy field, thereby increasing the intrinsic coercivity Hcj. The addition of CaCO3 not only acts as a flux but also contributes to the uniform diffusion and distribution of La and Co elements in the lattice.

[0032] In this invention, the mixing is preferably wet ball milling, the ball milling medium is preferably water and / or anhydrous ethanol, the ball-to-material ratio is preferably 3:1 to 8:1, specifically 5:1, the ball milling time is preferably 4 to 24 hours, specifically 12 hours; the rotation speed of the wet ball mill is preferably 250 rpm.

[0033] After mixing, the mixture preferably includes drying, followed by pre-firing. The drying is preferably carried out in an oven at a temperature of 80°C for 12 hours. After drying, the mixture is preferably passed through a 100-mesh sieve before pre-firing.

[0034] In this invention, the pre-firing is preferably carried out in an air atmosphere.

[0035] In this invention, the pre-firing temperature is preferably 1100~1320℃. When the target ferrite type is system A, the pre-firing temperature is preferably 1150~1280℃. When the target ferrite type is system B, the pre-firing temperature is preferably 1100~1250℃. When the target ferrite type is system C, the pre-firing temperature is preferably 1180~1320℃. The time is preferably 1~4h, specifically 1, 2, 3 or 4h, where time refers to the holding time.

[0036] In this invention, the heating rate from room temperature to the pre-firing temperature is preferably 5°C / min, and after the pre-firing is completed, the furnace is preferably cooled naturally.

[0037] In this invention, the preferred correspondence between the target ferrite type, the particle size of α-Fe2O3, and the pre-calcination parameters is shown in Table 1.

[0038] Table 1. Correspondence between target ferrite type, α-Fe2O3 particle size, and pre-calcination parameters.

[0039] After the pre-firing is completed, the ferrite magnetic powder is preferably subjected to coarse crushing, wet ball milling (ball milling), washing, and drying in sequence to obtain the ferrite magnetic powder.

[0040] In this invention, the coarse crushing is preferably crushed to <5mm.

[0041] In this invention, the wet ball milling time is preferably 6 to 36 hours, with deionized water as the medium, and zirconia ball milling beads (5 mm diameter: 10 mm mass ratio = 1:1) added at a ball-to-material ratio of 6:1. The ball milling is performed at 300 rpm (system A / B: 18 hours; system C: 24 hours). The target particle size D50 is preferably 0.8 to 5 μm, and more preferably 1.5 to 3 μm.

[0042] In this invention, the drying process preferably includes annealing to eliminate lattice defects and stresses introduced by ball milling, and to restore and optimize magnetic properties. The annealing temperature is preferably 800~1000℃, specifically 900℃, and the time is preferably 1~3h, specifically 2h.

[0043] After the annealing process is completed, it is preferably vacuum dried at 80°C for 6 hours, and then passed through a 325-mesh sieve to obtain the ferrite magnetic powder.

[0044] In this invention, the average grain size of the ferrite magnetic powder is preferably 0.5~10 μm, and the saturation magnetization Ms ≥ 55 emu / g (SrFe). 12 O 19 / BaFe 12 O 19 ) or ≥60 emu / g (La-Co doped system), intrinsic coercivity Hcj≥200kA / m.

[0045] After obtaining the ferrite magnetic powder, the present invention mixes the ferrite magnetic powder with a silane coupling agent for surface pretreatment to obtain surface-activated ferrite magnetic powder.

[0046] In this invention, the silane coupling agent is preferably used in the form of a silane coupling agent solution, the concentration of which is preferably 0.5 to 5 wt%, specifically 2 wt%, and the solvent of which is preferably an ethanol-water solution. This invention does not impose any special limitations on the concentration and amount of the ethanol-water solution.

[0047] In this invention, the silane coupling agent preferably includes one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), and γ-methacryloyloxypropyltrimethoxysilane (KH-570).

[0048] In this invention, the amount of the silane coupling agent is preferably 0.5-6% of the mass of the ferrite magnetic powder, more preferably 1-2%. In a specific embodiment of this invention, 1000g of the ferrite magnetic powder is added to 3000mL of a silane coupling agent solution with a concentration of 2.0wt%.

[0049] In this invention, the surface pretreatment is preferably carried out at room temperature to 80°C, specifically at 60°C, and the time is preferably 0.5 to 3 hours, specifically 2 hours. The surface pretreatment is preferably carried out under stirring conditions.

[0050] After the surface pretreatment is completed, the present invention preferably filters, washes and dries the obtained product in sequence to obtain the surface-activated ferrite magnetic powder, wherein the surface-activated ferrite magnetic powder is a ferrite magnetic powder activated by surface hydroxylation or amination.

[0051] In this invention, the drying is preferably vacuum drying, the vacuum drying temperature is preferably 60~100℃, specifically 80℃, and the drying time is preferably until constant weight is achieved.

[0052] This invention provides a functionalized metal-type single-walled carbon nanotube dispersion; the functionalized metal-type single-walled carbon nanotubes in the dispersion are metal-type single-walled carbon nanotubes that have undergone functional group activation treatment and surfactant treatment.

[0053] In this invention, the concentration of the functionalized metal-type single-walled carbon nanotube dispersion is preferably 0.1~5.0 mg / mL.

[0054] In this invention, the functionalized metal-type single-walled carbon nanotube dispersion is prepared by a method comprising the following steps: Metallic single-walled carbon nanotubes were subjected to functional group activation treatment to obtain functional group activated metallic single-walled carbon nanotubes. The functionalized metal single-walled carbon nanotubes, surfactant, and solvent are mixed to obtain the functionalized metal single-walled carbon nanotube dispersion.

[0055] In this invention, the preferred diameter of a single metallic single-walled carbon nanotube is 0.1~5.0 nm, the preferred length is 0.5~90 μm, the preferred purity is ≥90 wt%, and the preferred specific surface area is ≥400 m². 2 / g, the metallic SWCNT refers to single-walled carbon nanotubes with predominantly metallic conductivity. Its resistivity at room temperature is lower than that of non-metallic (semiconductor) SWCNTs, which is more conducive to the construction of thermally and electrically conductive networks.

[0056] In this invention, the functional group used in the functional group activation treatment preferably includes one or more of amino, carboxyl and ester groups, and the ester group more preferably includes -COOCH3. The metal single-walled carbon nanotubes used in the functional group activation treatment are preferably metal SWCNT-COOH, that is, the functional group used in the functional group activation treatment is a carboxyl group, and the carboxyl content in the metal SWCNT-COOH is preferably 2.5 at.

[0057] In this invention, the solvent preferably includes an organic solvent and / or water, and the organic solvent preferably includes one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP) and ethanol.

[0058] In this invention, the surfactant preferably includes one or more of sodium dodecylbenzenesulfonate (SDBS), Triton X-100, and polyvinylpyrrolidone (PVP).

[0059] In this invention, the amount of surfactant used is preferably 0.01 to 5 times the mass of the functional group-activated metal single-walled carbon nanotubes, specifically 1 time.

[0060] In this invention, the mixing is preferably carried out under ice bath conditions, and the time is preferably 10~60min, specifically 30min. The mixing is preferably ultrasonic dispersion, and the ultrasonic dispersion is preferably a cycle of 2s working and 2s intermittent.

[0061] After obtaining surface-activated ferrite magnetic powder and functionalized metal-type single-walled carbon nanotube dispersion, the present invention adds the surface-activated ferrite magnetic powder to the functionalized metal-type single-walled carbon nanotube dispersion to carry out a liquid-phase composite reaction to obtain ferrite@SWCNT composite powder.

[0062] In this invention, the preferred temperature for the liquid-phase composite reaction is 20~80℃, specifically 60℃, and the preferred time is 0.5~4h, specifically 2h. During the liquid-phase composite reaction, the surface-activated ferrite particles interact with the oxygen-containing functional groups and π-electron system on the surface of SWCNTs in the functionalized metal single-walled carbon nanotube dispersion through hydrogen bonding, van der Waals forces, and / or coordination bonds. This promotes the uniform coating of SWCNTs on the surface of the ferrite particles, and some SWCNTs form a bridging network structure between the particles.

[0063] In this invention, a catalyst is preferably added during the liquid-phase composite reaction. The catalyst preferably includes one or more of triethylamine, pyridine, and N,N-dimethylaminopyridine (DMAP) to promote the chemical coupling between ferrite surface functional groups and SWCNTs.

[0064] In this invention, the mass of the catalyst is preferably 0.1 to 1.0% of the mass of the functionalized metal single-walled carbon nanotubes.

[0065] In this invention, the liquid-phase composite reaction is preferably carried out under stirring and / or ultrasonic assistance, the stirring speed is preferably 500 rpm, and the ultrasonic power is preferably 200 W.

[0066] After the liquid-phase composite reaction is completed, the resulting mixture is preferably subjected to solid-liquid separation and vacuum drying in sequence to obtain the ferrite@SWCNT composite powder.

[0067] In this invention, the solid-liquid separation is preferably achieved through filtration or centrifugation.

[0068] In this invention, the vacuum drying temperature is preferably 60~100℃, and the time is preferably 2~24h.

[0069] After obtaining the ferrite@SWCNT composite powder, the present invention sequentially blends and granulates the ferrite@SWCNT composite powder with a thermoplastic polymer binder matrix, performs injection molding and magnetization to obtain the injection-molded bonded ferrite magnet.

[0070] In this invention, the raw materials, based on surface-activated ferrite magnetic powder, functionalized metallic single-walled carbon nanotubes, and thermoplastic polymer binder matrix, preferably include the following components by mass percentage: 80-93% (more preferably 85-91%) of surface-activated ferrite magnetic powder, 0.05-3% (more preferably 0.1-1.5%) of functionalized metallic single-walled carbon nanotubes, and 6.95-17% (more preferably 8.5-14%) of thermoplastic polymer binder matrix.

[0071] In this invention, the thermoplastic polymer binder preferably includes one or more of nylon 6 (PA6), nylon 12 (PA12), and polyphenylene sulfide (PPS). When the thermoplastic polymer binder preferably includes PPS, drying is preferably performed before injection molding. The drying temperature is preferably 120~150°C, and the drying time is preferably 4~8 hours. The mold temperature used for injection molding is increased to 130~160°C to promote the full crystallization of PPS.

[0072] In this invention, the raw materials preferably further include processing aids, and the mass percentage of the processing aids in the raw materials is preferably 0 to 2% and not 0, more preferably 0.2 to 1%.

[0073] In this invention, the processing aid preferably includes one or more of calcium stearate, zinc stearate, vinyl bis-stearamide (EBS), silicone powder, antioxidant 1010, and antioxidant 168.

[0074] In this invention, the ferrite@SWCNT composite powder and the thermoplastic polymer binder matrix are preferably added to a high-speed mixer and mixed at a speed of 500-10000 rpm for 5-30 minutes. Then, the mixture is melted and granulated by a twin-screw extruder. The extrusion temperature of the granulation is preferably 20-80°C above the melting point of the thermoplastic polymer binder matrix, and the screw speed is preferably 50-300 rpm to obtain ferrite@SWCNT / polymer composite granules. The ferrite@SWCNT / polymer composite granules are preferably dried before injection molding.

[0075] In this invention, the drying temperature is preferably 80~120℃, and the drying time is preferably 2~6h.

[0076] In this invention, the screw length-to-diameter ratio of the twin-screw extruder is preferably 30:1 to 48:1, specifically 40:1. The screw preferably adopts a strong shear combination design to promote the full wetting and coating of the ferrite@SWCNT composite powder by the thermoplastic polymer binder matrix. From the feed port to the die, the temperature of each zone of the twin-screw extruder is preferably 230 / 240 / 245 / 250 / 250 / 245 / 240℃ (PA6), 190 / 200 / 210 / 215 / 215 / 210 / 200℃ (PA12), or 290 / 300 / 310 / 315 / 315 / 310 / 300℃ (PPS).

[0077] In this invention, the injection molding parameters preferably include: a barrel temperature 10-100°C above the melting point of the thermoplastic polymer binder matrix; an injection pressure of 60-150 MPa, specifically 100, 110, or 130 MPa; a holding pressure of 40-100 MPa, specifically 60, 70, or 90 MPa; a mold temperature of 60-150°C, specifically 60, 80, or 145°C; a cooling time of 0.1-60 min (specifically 25 or 30 s); and a barrel temperature from nozzle to feeding section of 245 / 250 / 255 / 250°C (PA6), 210 / 215 / 220 / 215°C (PA12), or 300 / 315 / 320 / 310°C (PPS).

[0078] In this invention, the injection molding is preferably performed in an injection molding machine.

[0079] In this invention, the injection molding mold is preferably a mold in which an orientation magnetic field is applied. During the injection molding process or the holding pressure stage, an orientation magnetic field of 0.1~1.5T (specifically 0.8T) is applied by an electromagnetic coil or permanent magnet set around the mold cavity, so that the ferrite magnetic powder particles are oriented and arranged along the direction of the magnetic field, thereby improving the remanence and magnetic energy product of the magnet.

[0080] In this invention, the magnetization is preferably carried out under a pulsed magnetic field of 2 to 8 T, specifically 2, 4, 6 or 8 T.

[0081] In this invention, the magnetization is preferably performed in a pulse magnetizer.

[0082] The present invention also provides an injection-molded bonded ferrite magnet prepared by the preparation method described above, comprising functionalized metallic single-walled carbon nanotubes and ferrite magnetic powder particles. The functionalized metallic single-walled carbon nanotubes exist in a core-shell coating layer on the surface of the ferrite magnetic powder particles and / or in a network distribution morphology penetrating between the ferrite magnetic powder particles. The ferrite magnetic powder particles have a bimodal grain size distribution, and the ferrite magnetic powder particles include small grains and large grains. The small grains have a grain size of 0.5~2μm, and the large grains have a grain size of 3~10μm.

[0083] Figure 1 This is a schematic diagram of the injection-molded bonded ferrite magnet of the present invention. Figure 1 In the diagram, ① represents ferrite magnetic powder particles, ② represents functionalized metallic single-walled carbon nanotubes, and ③ represents a thermoplastic polymer binder matrix.

[0084] In this invention, the flexural strength of the injection-molded bonded ferrite magnet is preferably ≥55 MPa, the thermal conductivity is preferably ≥0.85 W / (m·K), the remanence Br is preferably ≥190 mT, and the intrinsic coercivity Hcj is preferably ≥180 kA / m.

[0085] This invention provides an injection-molded bonded ferrite permanent magnet prepared by injection molding using high-performance ferrite magnetic powder prepared with the assistance of inorganic compound additives as the magnetic filler, functionalized metallic SWCNT as the functional reinforcing phase, and PA6, PA12, PPS, or blends thereof as the thermoplastic polymer binder matrix. This invention has the following three innovative aspects: (1) Raw material-level control of intrinsic properties of ferrite magnetic powder: α-Fe2O3 with different morphologies and particle size distributions (10nm~200μm) is used as the iron source precursor. By introducing inorganic compound additives, such as CaCO3, La2O3, Co3O4, etc., the morphology, size and magnetocrystalline anisotropy of magnetic powder grains are precisely controlled during the ferrite pre-calcination stage. (2) Construction of ferrite-SWCNT structured composite interface: By pre-compositing functionalized metallic SWCNTs with ferrite magnetic powder in liquid phase, a magnetic powder-functionalized SWCNT network structured composite interface is constructed, which is then blended and granulated with a thermoplastic polymer binder matrix, and finally injection molded. (3) Hybrid magnetic circuit cost reduction application: The resulting low-cost injection-molded bonded ferrite magnet can be used in conjunction with high-cost rare earth permanent magnets in the motor magnetic circuit, replacing rare earth magnets in the sparse magnetic field area, and achieving a significant cost reduction effect.

[0086] In permanent magnet motors, especially high-performance servo motors and drive motors for new energy vehicles, magnetic circuit design typically involves complex magnetic flux distribution. Magnetic flux is concentrated and dense near the operating point of the permanent magnet, but sparsely distributed at the pole edges, leakage regions, and auxiliary magnetic circuit sections. Currently, the industry standard is to use high-performance sintered neodymium iron boron (NdFeB) or samarium cobalt (SmCo) permanent magnets exclusively. However, these high-cost magnets are actually in a state of overperformance in regions with sparse magnetic flux, resulting in significant material waste. For example, in a 100kW drive motor, rare-earth permanent magnets account for 40% to 60% of the total material cost, while 20% to 35% of the magnet volume is in the low flux density utilization region.

[0087] Hybrid magnetic circuit matching of low-cost bonded ferrites and high-cost rare-earth permanent magnets—that is, using high-performance rare-earth permanent magnets in dense magnetic field lines and low-cost ferrite magnets in edge and low-flux areas—is a highly cost-effective solution for reducing motor costs. However, to achieve this, bonded ferrite magnets must possess the following key properties: (i) sufficiently high remanence and intrinsic coercivity to match system requirements; (ii) excellent mechanical toughness to accommodate mechanical coupling with rigid rare-earth magnets; (iii) good thermal conductivity to cope with localized heat buildup; and (iv) high dimensional accuracy and the ability to form complex shapes to meet the requirements of irregularly shaped magnetic circuits. Existing bonded ferrite products have significant shortcomings in all four aspects, severely restricting the engineering application of hybrid magnetic circuit solutions.

[0088] This invention also provides a hybrid magnetic circuit structure, comprising the injection-molded bonded ferrite magnet and rare-earth permanent magnet described in the above technical solution. The injection-molded bonded ferrite magnet of this invention improves the intrinsic properties of ferrite magnetic powder while significantly enhancing the magnet's mechanical properties, processing flowability, and thermal conductivity, making it a novel bonded ferrite magnet material system suitable for hybrid magnetic circuit design scenarios.

[0089] The present invention preferably uses high-performance rare-earth permanent magnets in the working air gap region where magnetic lines of force are dense, and uses injection-molded bonded ferrite magnets as described in the present invention in the magnetic pole edges, leakage magnetic regions and auxiliary magnetic circuit parts where magnetic lines of force are sparse, so as to achieve the optimal balance between the cost and performance of the motor magnetic circuit. It is widely used in permanent magnet components in permanent magnet motor rotors, sensor magnetic rings and precision drive devices. Figure 3 This is a schematic diagram showing the distribution of high-performance permanent magnets and injection-molded bonded ferrite magnets.

[0090] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0091] Figure 2 The flowchart for preparing the injection-molded bonded ferrite magnet in this embodiment of the invention is as follows: α-Fe2O3 and inorganic compound additives are sequentially mixed and pre-calcined to obtain ferrite magnetic powder. The ferrite magnetic powder is then mixed with a silane coupling agent for surface pretreatment to obtain surface-activated ferrite magnetic powder. A functionalized metal-type single-walled carbon nanotube dispersion is provided. The surface-activated ferrite magnetic powder is added to the functionalized metal-type single-walled carbon nanotube dispersion for a liquid-phase composite reaction to construct a ferrite@SWCNT composite system. Then, solid-liquid separation and vacuum drying are performed to obtain ferrite@SWCNT composite powder. The ferrite@SWCNT composite powder and a thermoplastic polymer bonding matrix are sequentially subjected to high-speed co-mixing and twin-screw melt blending and granulation. The resulting granules are dried and then injection-molded, and finally magnetized in a pulsed magnetic field to obtain the injection-molded bonded ferrite magnet.

[0092] The raw material specifications in this embodiment of the invention are shown in Table 2.

[0093] Table 2 Raw Material Specifications

[0094] Example 1 SrFe 12 O 19 @SWCNT-0.3 / PA6 system (SF-1+KH-550) Preparation process of ferrite magnetic powder: For ingredient preparation and mixing, weigh each raw material according to SF-1 in Table 1, add it to the ball mill jar, use anhydrous ethanol as the ball milling medium, add zirconia ball milling beads at a ball-to-material mass ratio of 5:1, and ball mill at 250 rpm for 12 hours. Figure 4 This is a SEM image of nano-sized α-Fe₂O₃. Figure 5 This is a SEM image of submicron-sized α-Fe₂O₃. Figure 6 SEM image of micron-sized α-Fe2O3; Drying: The ball-milled slurry was dried in an oven at 80℃ for 12 hours and then passed through a 100-mesh sieve; Pre-calcination: The dried powder is placed in a muffle furnace and pre-calcined in an air atmosphere according to the pre-calcination parameters listed in Table 1. The heating rate is 5℃ / min, and the powder is cooled naturally with the furnace. Fine grinding: The pre-fired blocks are coarsely crushed to <5mm, and zirconia grinding beads (5mm diameter: 10mm mass ratio = 1:1) are added with deionized water as the medium at a ball-to-material ratio of 6:1. The mixture is then ball-milled at 300rpm (system A / B: 18h; system C: 24h). The target particle size D50 is 1.5~3.0μm. Annealing: The finely ground magnetic powder was annealed in air at 900°C for 2 hours to eliminate the lattice stress introduced by ball milling; Drying and sieving: After annealing, the magnetic powder was vacuum dried at 80℃ for 6 hours and then sieved through a 325-mesh sieve to obtain the finished ferrite magnetic powder. The SEM image of the obtained ferrite magnetic powder is shown below. Figure 7 As shown, ferrite magnetic powder is mainly composed of hexagonal plate-shaped grains with relatively complete grain morphology and exhibits a bimodal grain size characteristic with both large and small grains coexisting.

[0095] The preparation of injection-molded bonded ferrite magnets includes the following steps: Step S1: Add 1000g of SF-1 ferrite magnetic powder to 3000mL of a 2.0wt% KH-550 silane coupling agent ethanol / water solution (ethanol:water volume ratio = 9:1), and mechanically stir in a 60℃ water bath for 2h at a stirring speed of 400rpm. After treatment, filter, wash three times with anhydrous ethanol, and vacuum dry at 80℃ for 6h to obtain surface amino-activated SF-1 ferrite magnetic powder.

[0096] Step S2: Add 3.0g of metallic SWCNT-COOH and 3.0g of SDBS to 600mL of deionized water, and use an ultrasonic cell disruptor at 300W power to ultrasonically disperse for 30min (2s working / 2s rest cycle) under ice bath conditions to obtain a functionalized metallic single-walled carbon nanotube stable aqueous dispersion with a concentration of 5.0mg / mL.

[0097] Step S3: Slowly add the surface-activated ferrite magnetic powder obtained in Step S1 to the functionalized metallic single-walled carbon nanotube dispersion obtained in Step S2 (mass ratio of surface-activated ferrite magnetic powder:functionalized metallic single-walled carbon nanotubes = 1000:3). Mechanically stir (500 rpm) in a 60℃ water bath and then treat with ultrasound (200W) for 2 hours to carry out the liquid-phase composite reaction. After the reaction is complete, allow it to cool naturally to room temperature.

[0098] Step S4: Vacuum filter the mixture obtained in step S3, wash it three times with deionized water, and dry the filter cake under vacuum at 80°C for 8 hours to obtain SF-1@SWCNT (SWCNT content 0.3wt%) composite powder. Figure 8 The SEM image of the SF-1@SWCNT composite powder shows that SWCNTs are attached and wrapped around the surface of the ferrite magnetic powder in the form of fine filaments and bridge adjacent particles, indicating that the two have been effectively composited. 900g of the prepared SF-1@SWCNT composite powder, 97g of PA6 granules, 2g of calcium stearate, and 1g of antioxidant 1010 were added to a high-speed mixer and mixed at 2000rpm for 10min. The mixture was then melt-blended and granulated using a twin-screw extruder (40:1 L / D ratio, high-shear combination screws). The temperatures in each zone were set to 230 / 240 / 245 / 250 / 250 / 245 / 240℃ (from the feed port to the die), and the screw speed was 200rpm. The extruded strip was cooled in a water bath and then granulated to obtain SF-1@SWCNT / PA6 composite granules (90wt% ferrite@SWCNT, 0.27wt% net SWCNT content).

[0099] Step S5: Dry the composite granules at 100℃ for 4 hours, and then use an injection molding machine for injection molding. The molding conditions are: barrel temperature 245 / 250 / 255 / 250℃ (from nozzle to feeding section), injection pressure 110MPa, holding pressure 70MPa, holding time 15s, mold temperature 80℃, and cooling time 30s to obtain standard test strips and annular magnet green blanks.

[0100] Step S6: Place the green magnet blank in a pulse magnetizer and magnetize it under a 4T pulse magnetic field to obtain the finished injection-molded bonded ferrite magnet.

[0101] Example 2 SrFe 12 O 19 @SWCNT-0.3 / PA6 system (SF-2+KH-550, high CaCO3) The difference from Example 1 is that SF-2 magnetic powder is used instead of SF-1 magnetic powder. The remaining steps and process parameters are the same as in Example 1.

[0102] Example 3 SrFe 12 O 19 @SWCNT-0.3 / PA6 system (SF-3+KH-550, needle-like precursor) The difference from Example 1 is that SF-3 magnetic powder is used instead of SF-1 magnetic powder. The remaining steps and process parameters are the same as in Example 1.

[0103] Example 4 SrFe 12 O 19 @SWCNT-0.1 / PA6 system (low-functionalized metallic single-walled carbon nanotubes) The difference from Example 1 is that the feed mass ratio of surface-activated ferrite magnetic powder to functionalized metallic single-walled carbon nanotubes is 1000:1. The net SWCNT content in the resulting magnet is 0.09 wt%. The remaining steps and process parameters are the same as in Example 1.

[0104] Example 5 SrFe 12 O 19 @SWCNT-1 / PA6 system (highly functionalized metallic single-walled carbon nanotubes) The difference from Example 1 is that the feed mass ratio of surface-activated ferrite magnetic powder to functionalized metallic single-walled carbon nanotubes is 1000:10. The net SWCNT content in the resulting magnet is 0.9 wt%. The remaining steps and process parameters are the same as in Example 1.

[0105] Example 6 SrFe 12 O 19 @SWCNT-0.3 / PA12 system (SF-1+PA12 matrix) The difference from Example 1 is that the polymer matrix used in step S4, when co-blending and granulating, is PA12 (77g).

[0106] The temperatures in each zone of the twin-screw extruder were set to 190 / 200 / 210 / 215 / 215 / 210 / 200℃, and the screw speed was 180 rpm. The composite granules were dried at 90℃ for 4 hours. The injection molding conditions were: barrel temperature 210 / 215 / 220 / 215℃, injection pressure 100 MPa, holding pressure 60 MPa, mold temperature 60℃, and cooling time 25 seconds.

[0107] The composite granules contain 92 wt% SF-1@SWCNT and a net SWCNT content of 0.276 wt%. All other process parameters are the same as in Example 1.

[0108] Example 7 SrFe 12 O 19 @SWCNT-0.3 / PPS system (SF-1+PPS matrix) The difference from Example 1 is that: in step S1, the coupling agent is changed to KH-560 (concentration 2.5wt%, treated at 70℃ for 2.5h); in step S4, the polymer matrix is ​​PPS (dosage 138g).

[0109] In step S2, the solvent is DMF (instead of water), and the surfactant is PVP (instead of SDBS). After liquid-phase recombination, centrifugation is performed (8000 rpm, 10 min). The solid is washed twice with DMF and dried under vacuum at 100 °C for 10 h.

[0110] The temperature settings for each zone of the twin-screw extruder are 290 / 300 / 310 / 315 / 315 / 310 / 300℃, and the screw speed is 150 rpm. The composite granules are dried at 130℃ for 6 hours. The injection molding conditions are: barrel temperature 300 / 315 / 320 / 310℃, injection pressure 130 MPa, holding pressure 90 MPa, mold temperature 145℃, and cooling time 40 seconds.

[0111] The composite granules contain 86 wt% SF-1@SWCNT and 0.258 wt% SWCNT net content.

[0112] Example 8 BaFe 12 O 19 @SWCNT-0.3 / PA6 system (BF-1) The difference from Example 1 is that BF-1 barium ferrite magnetic powder is used instead of SF-1 strontium ferrite magnetic powder. The remaining steps and process parameters are the same as in Example 1.

[0113] Example 9 BaFe 12 O 19 @SWCNT-0.3 / PA6 system (BF-2, highly lamellar precursor) The difference from Example 1 is that BF-2 barium ferrite magnetic powder (30wt% micron-sized flake α-Fe2O3) was used instead of SF-1. The remaining steps and process parameters are the same as in Example 1.

[0114] Example 10 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PA6 system (LCSF-1) The difference from Example 1 is that LCSF-1 is used instead of SF-1, and 0.05 g of DMAP is added as a coupling catalyst during liquid-phase recombination in step S3. The remaining steps and process parameters are the same as in Example 1.

[0115] Example 11 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PA6 system (LCSF-2) The difference from Example 1 is that LCSF-2 is used instead of SF-1. The remaining steps and process parameters are the same as in Example 1.

[0116] Example 12 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PA12 system (LCSF-1+PA12) The difference from Example 10 is that PA12 (77g) was used instead of PA6 in step S4. The twin-screw extrusion and injection molding parameters were the same as in Example 6. The LCSF-1@SWCNT content in the composite granules was 92wt%.

[0117] Example 13 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PPS system (LCSF-1+PPS) The difference from Example 10 is that the coupling agent in step S1 is replaced with KH-560, and PPS (138g) is used in step S4. The granulation and injection molding parameters are the same as in Example 7. The LCSF-1@SWCNT content in the composite granules is 86wt%.

[0118] Example 14 SrFe 12 O 19 @SWCNT-0.3 / PA6 system (SF-1+ magnetic field orientation molding) The difference from Example 1 is that, in step S5, during the injection molding process, an electromagnetic coil is placed around the mold cavity to generate a 0.8T orientation magnetic field, which is continuously applied for 10 seconds during the holding pressure stage, after which the magnetic field is turned off to complete the remaining cooling. The remaining process parameters are the same as in Example 1.

[0119] Example 15 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PA6 system (LCSF-1+ magnetic field orientation molding) The difference from Example 10 is that, during the injection molding process in step S5, an electromagnetic coil is placed around the mold cavity to generate a 0.8T orientation magnetic field (same as Example 14). The remaining process parameters are the same as in Example 10.

[0120] Example 16 La-Co-SrFe 12 O 19 @SWCNT-0.3 / PA6 system (LCSF-3) The difference from Example 1 is that LCSF-3 is used instead of SF-1. The remaining steps and process parameters are the same as in Example 1.

[0121] Comparative Example 1: SrFe without SWCNT 12 O 19 / PA6 system The difference from Example 1 is that steps S2 and S3 are completely omitted, and SWCNT is not added. The SF-1 ferrite magnetic powder after surface activation in step S1 is directly blended with PA6 and processing aids in the same proportion as in Example 1, granulated, and injection molded.

[0122] Comparative Example 2: Direct mechanical blending of SWCNTs (SF-1 system) The difference from Example 1 is that the liquid-phase composite process in steps S2 and S3 is omitted. Instead, the surface-activated SF-1 magnetic powder (1000g), functionalized metallic single-walled carbon nanotube powder (3.0g), PA6 granules, and processing aids are directly mixed in a high-speed mixer at 3000rpm for 20min, and then melt-blended and granulated in a twin-screw extruder. That is, SWCNTs are not pre-dispersed and pre-structured in the liquid phase.

[0123] Comparative Example 3: SrFe prepared from a single-particle-size α-Fe₂O₃ precursor 12 O 19 / PA6 system The ferrite magnetic powder was prepared using only spherical α-Fe₂O₃ with an average particle size of 2.0 μm (without using nano- or micron-sized precursors), and the rest of the formulation was the same as SF-1. The pre-calcination temperature was adjusted to 1250 °C / 2 h to ensure sufficient reaction. This magnetic powder was labeled SF-REF. Magnets were then prepared according to the process in Example 1 (including SWCNT liquid-phase composite).

[0124] Comparative Example 4: SrFe without added inorganic compound additives 12 O 19 / PA6 system During the preparation of ferrite magnetic powder, no CaCO3 was added; only α-Fe2O3 (a multi-particle size mixture as in the SF-1 formulation) and SrCO3 were used in stoichiometric proportions. The pre-calcination temperature needed to be increased to 1280℃ / 2h. This magnetic powder was labeled SF-NC. Magnets were then prepared according to the process in Example 1 (including SWCNT liquid-phase composite).

[0125] The performance testing methods are shown in Table 3.

[0126] Table 3 Performance Testing Methods

[0127] Table 4 shows the basic magnetic properties of each ferrite magnetic powder (after pre-heating and annealing, without being bonded to the thermoplastic polymer matrix).

[0128] Table 4. Basic magnetic properties of various ferrite magnetic powders

[0129] The performance test results of each embodiment and comparative example are shown in Table 5.

[0130] Table 5 Performance test results of each embodiment and comparative example

[0131] Results analysis: (1) The SWCNT liquid phase composite process significantly improves mechanical properties.

[0132] Taking Example 1 and Comparative Example 1 as an example, after adding only 0.27 wt% of metallic SWCNT (through liquid-phase pre-composite process), the flexural strength increased from 42.8 MPa to 72.3 MPa (+68.9%), and the impact strength increased from 4.5 kJ / m. 2 Increased to 8.5 kJ / m 2 (+88.9%). Thermal conductivity increased from 0.70 W / (m·K) to 1.02 W / (m·K) (+45.7%). MFI increased from 13.8 g / 10 min to 19.2 g / 10 min (+39.1%). This fully demonstrates the synergistic enhancement effect of the ferrite@SWCNT core-shell / network structure.

[0133] (2) The criticality of liquid phase precomposite process.

[0134] The flexural strength of Comparative Example 2 (direct mechanical blend of SWCNT) was only 53.5 MPa, far lower than the 72.3 MPa of Example 1, and the magnetic properties also decreased (Br decreased from 218 mT to 210 mT, and Hcj decreased from 262 kA / m to 258 kA / m). This indicates that without liquid-phase pre-structured composite, SWCNT cannot effectively encapsulate ferrite particles, and most of them agglomerate into bundles in the matrix, weakening the reinforcement effect and introducing defects.

[0135] (3) Advantages of α-Fe2O3 precursors with multiple morphologies and particle sizes.

[0136] The magnetic properties of Comparative Example 3 (single-size precursor) were significantly lower than those of Example 1: Br (208 vs 218 mT), Hcj (232 vs 262 kA / m), and BHmax (7.5 vs 8.5 kJ / m). 3 The bimodal grain distribution formed by the multi-size mixed precursor after pre-calcination balances high remanence and high coercivity, a synergistic optimization that cannot be achieved with a single particle size. Furthermore, the magnetic powder in Comparative Example 3 requires a higher pre-calcination temperature (1250℃ vs 1220℃) for a complete reaction, indicating that the highly active nano-components of the multi-size precursor help lower the solid-phase reaction temperature.

[0137] (4) The significant effects of inorganic compound additives (CaCO3).

[0138] The Hcj of Comparative Example 4 (without CaCO3) was only 178 kA / m, far lower than the 262 kA / m of Example 1 (a reduction of 32.1%), and Br also decreased from 218 mT to 202 mT. The role of CaCO3 in pre-calcination includes: (i) decomposing into CaO and then partially converting CaO into Ca2+. 2+(ii) It enters the crystal lattice to optimize grain morphology; (iii) it acts as a flux to promote ion diffusion and reduce reaction temperature; and (iv) it inhibits abnormal grain growth, making the grain size distribution more uniform. In Example 2, Hcj was further increased to 278 kA / m, verifying the positive regulatory effect of CaCO3 addition on coercivity.

[0139] (5) La-Co doping significantly improves coercivity.

[0140] Example 10 (La-Co-doped Sr ferrite) achieved an Hcj of 378 kA / m, a 44.3% improvement compared to Example 1 (undoped, 262 kA / m). Example 11 showed an even higher Hcj of 415 kA / m, representing an improvement of 58.4%. 3+ Replace Sr 2+ and Co 2+ / 3+ Fe replacement 3+ The combined doping significantly enhances the magnetocrystalline anisotropy field, which is one of the most effective ways to improve the coercivity of ferrites. High Hcj makes the La-Co doped system particularly suitable for applications with a high risk of demagnetization at high temperatures (such as locations near rare-earth permanent magnets in hybrid magnetic circuits).

[0141] (6) The influence of α-Fe2O3 morphology on magnetic properties.

[0142] Example 3 (needle-shaped micron-sized precursor) showed the highest Br (221 mT), indicating that the needle-shaped precursor facilitates the formation of grains with texture orientation during pre-firing, thus enhancing remanence. Example 9 showed a higher Hcj (240 kA / m) than Example 8 (228 kA / m), suggesting that the plate-shaped precursor facilitates a more uniform grain size distribution and reduces the negative impact of abnormally large grains on coercivity.

[0143] (7) Verification of multi-matrix applicability.

[0144] Examples 1 (PA6), 6 (PA12), and 7 (PPS) all successfully yielded bonded ferrite magnets with excellent overall performance, demonstrating the versatility of the method of this invention for different thermoplastic polymer matrices. The PA12 system (Example 6) exhibited the highest impact strength (14.8 kJ / m). 2 The PPS system (Example 7) has the highest bending strength (86.3 MPa), making it suitable for high-vibration conditions.

[0145] (8) Magnetic performance gain of magnetic field orientation.

[0146] In Example 14, Br increased from 218 mT to 258 mT (+18.3%), and BHmax increased from 8.5 kJ / m 3Increased to 11.8 kJ / m 3 (+38.8%). In Example 15, Br increased from 202 mT to 242 mT (+19.8%), and BHmax increased from 7.8 kJ / m 3 Increased to 10.8 kJ / m 3 (+38.5%). This indicates that the coating layer of SWCNT did not hinder the rotational orientation of the ferrite magnetic powder during the injection molding process.

[0147] Summary of performance comparison between the present invention and traditional solutions To demonstrate the effectiveness of the various technical measures of this invention in improving the overall performance of bonded ferrite magnets, a multi-dimensional systematic comparison is conducted between the traditional solution and the solution of this invention. The traditional solution is defined as: conventional injection molding of bonded ferrite magnets using a single-size spherical α-Fe2O3 precursor, without adding any inorganic compound additives, without adding SWCNTs, and without magnetic field orientation. The solution of this invention is defined as: a comprehensive optimization scheme using multi-morphology, multi-size α-Fe2O3 precursors + inorganic compound additives + SWCNT liquid-phase pre-structured composite + magnetic field orientation molding. See Tables 6-8. It can be seen that this invention achieves a comprehensive breakthrough in the four dimensions of bonded ferrite magnets—magnetic properties, mechanical properties, thermal conductivity, and processing performance—through four key technological innovations: ① multi-morphology, multi-size α-Fe2O3 precursor design; ② raw material-level control of inorganic compound additives; ③ functionalized metallic SWCNT liquid-phase pre-structured composite; and ④ magnetic field orientation molding during the injection molding process. Among them, the bending strength is doubled (+107%), the thermal conductivity is nearly doubled (+187%), and the coercivity can be increased by nearly 80% (La-Co doped system), while maintaining good injection molding processability (MFI is increased by up to 70%), providing a solid material basis for low-cost ferrites to replace some high-cost rare earth permanent magnets in hybrid magnetic circuits.

[0148] Table 6. Comparison of overall magnet performance between the present invention and traditional solutions.

[0149] Note: For the traditional scheme, the Br / Hcj / BHmax values ​​of Comparative Example 3 (single particle size precursor + SWCNT liquid phase composite) are used as the magnetic performance benchmark (because its magnetic powder preparation conditions are closest to the traditional industrial route). The mechanical / thermal / MFI data are used as the benchmark of Comparative Example 1 (without SWCNT) (because the traditional scheme does not contain SWCNT).

[0150] Table 7 Performance improvement of ferrite magnetic powder layer (after pre-heating and annealing, without thermoplastic polymer binder matrix)

[0151] Table 8 Summary of the core advantages of the integrated solution of the present invention compared with traditional solutions

[0152] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an injection-molded bonded ferrite magnet, characterized in that, Includes the following steps: α-Fe2O3 and inorganic compound additives are mixed and pre-calcined sequentially to obtain ferrite magnetic powder, wherein the particle size of α-Fe2O3 is 10nm~200μm; The ferrite magnetic powder is mixed with a silane coupling agent and subjected to surface pretreatment to obtain surface-activated ferrite magnetic powder. A functionalized metal-type single-walled carbon nanotube dispersion is provided; wherein the functionalized metal-type single-walled carbon nanotubes in the dispersion are metal-type single-walled carbon nanotubes that have undergone functional group activation treatment and surfactant treatment. The surface-activated ferrite magnetic powder was added to a functionalized metal single-walled carbon nanotube dispersion to carry out a liquid-phase composite reaction, thereby obtaining ferrite@SWCNT composite powder. The ferrite@SWCNT composite powder and the thermoplastic polymer binder matrix are sequentially blended, granulated, injection molded, and magnetized to obtain the injection-molded bonded ferrite magnet.

2. The preparation method according to claim 1, characterized in that, The α-Fe2O3 comprises the following components in parts by mass: 5-20 parts by mass of nano-sized α-Fe2O3, 50-80 parts by mass of submicron-sized α-Fe2O3, and 10-30 parts by mass of micron-sized α-Fe2O3. The particle size of the nano-sized α-Fe2O3 is 10-500 nm, the particle size of the submicron-sized α-Fe2O3 is 0.5-10 μm, and the particle size of the micron-sized α-Fe2O3 is 10-200 μm.

3. The preparation method according to claim 1, characterized in that, The inorganic compound additives include one or more of SrCO3, BaCO3, La2O3, Co2O3, Co3O4, and fluxing agents.

4. The preparation method according to claim 1 or 3, characterized in that, The pre-firing temperature is 1100~1320℃, and the time is 1~4h.

5. The preparation method according to claim 1, characterized in that, The functional groups used in the functional group activation treatment include one or more of amino, carboxyl, and ester groups.

6. The preparation method according to claim 1, characterized in that, Based on surface-activated ferrite magnetic powder, functionalized metallic single-walled carbon nanotubes, and thermoplastic polymer binder matrix as raw materials, the raw materials include the following components by mass percentage: 80-93% surface-activated ferrite magnetic powder, 0.05-3% functionalized metallic single-walled carbon nanotubes, and 6.95-17% thermoplastic polymer binder matrix.

7. The preparation method according to claim 1, characterized in that, The raw materials also include processing aids, wherein the mass percentage of the processing aids in the raw materials is 0-2% and not 0.

8. The preparation method according to claim 1, characterized in that, The temperature of the liquid-phase composite reaction is 20~80℃, and the time is 0.5~4h.

9. The injection-molded bonded ferrite magnet prepared by the preparation method according to any one of claims 1 to 8, characterized in that, The material includes functionalized metallic single-walled carbon nanotubes and ferrite magnetic powder particles. The functionalized metallic single-walled carbon nanotubes exist in a core-shell coating layer on the surface of the ferrite magnetic powder particles and / or in a network distribution pattern that runs through the ferrite magnetic powder particles. The ferrite magnetic powder particles have a bimodal grain size distribution, and the ferrite magnetic powder particles include small grains and large grains. The small grains have a grain size of 0.5~2μm, and the large grains have a grain size of 3~10μm.

10. A hybrid magnetic circuit structure comprising the injection-molded bonded ferrite magnet and rare-earth permanent magnet as described in claim 9.